Analysis of Fourth Grade Elementary Students’ Mathematical Problem-Solving Abilities - Dita Nurdianti; Sugiyono; Suryatin (STEAM Journal For Elementary School Education, 2025)
The purpose of this study is to describe students’ mathematical problem-solving abilities and to identify the factors that influence them. This research is a qualitative study with a descriptive approach conducted at SDN 1 Mendolo Kidul, with fourth-grade students and their teacher as research subjects. Data were collected using tests, interviews, and documentation. The validity of the data was ensured through source triangulation and technique triangulation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that students in the high category tend to apply all problem-solving steps correctly, while those in the medium category still make mistakes in some steps. In contrast, students in the low category make errors in almost all of the steps. The factors that influence students’ mathematical problem-solving abilities include experiential, affective, and cognitive factors. The results of this study can serve as a reference for teachers in designing more effective learning strategies to improve students’ mathematical problem-solving abilities. In addition, the findings can assist schools in developing remedial programs tailored to students’ ability levels. This study also contributes to providing empirical information on the variation of mathematical problem-solving abilities at the elementary school level and the influencing factors, which can serve as a reference for further research in this field.